Pengaruh Dana Pihak Ketiga, Likuiditas, dan Islamicity Performance Index terhadap Harga Saham : Studi pada Bank Syariah Indonesia 2021-2025 - Yulin Nur Hidayah; Bambang Sugeng Dwiyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Bank Syariah Indonesia (BSI) faces challenges in optimizing financial performance and market valuation following the merger process in 2021. This study aims to analyze the influence of Third Party Funds, liquidity, and Islamicity Performance Index on BSI stock prices during the period 2021-2025. The research employs multiple linear regression analysis method using monthly data from BSI financial reports and stock price data from the Indonesia Stock Exchange. The results indicate that Third Party Funds have a negative but non-significant effect on BSI stock prices, suggesting that increases in Third Party Funds do not automatically enhance stock valuation as investors are concerned about the profit-sharing burden that must be paid. Liquidity has a positive and significant effect on stock prices, demonstrating that fund distribution efficiency is the primary factor evaluated by investors. The Islamicity Performance Index has a negative and significant effect on stock prices, confirming that investors interpret high sharia compliance indices as reducing profitability for shareholders. This study confirms that investors in evaluating Bank Syariah Indonesia stocks prioritize operational efficiency over operational scale or sharia compliance orientation.